Defects treatment on ZnO nanorods grown by hydrothermal method in application of DSSC - Sun, Hui Yuan. (2010)
The world’s energy needs has been increasing steeply since industrial revolution. The world economic is so conditioned on oil, but oil will slowly dry up. Continue increasing demand of energy will cause serious environment issues, particularly climate problem. And the lack of oil recourses will drive electrical power to a higher price. “Keeping 2050 in mind” as asked by K.R. Sreenivasan, “where is this energy going to come from?” [1] One possible solution to energy crisis is to exploit the use of renewable energy especially solar energy. And for this reason, solar cell has been a hot research area recently. One type of solar cell is fabricated based on nanostructures as electrodes like nanorods, nanotube,and so on which extends the electrode surface area comparing to flat surface electrode. In addition, nanoparticles often exhibit unexpected visible properties because they are small enough to confine their electrons and produce quantum effects, surface Plasmon resonance and so on. These novel phenomenons are expected to bring breakthrough to conventional devices’ performance. DSSC is an example that applies nanoparticles working as electrodes in solar cell. ZnO nanostructures have attracted a lot of interests for two reasons. First, it owns excellent properties like large exciton binding energy(60 meV), high electromechanical coupling constant and resistivity to harsh environment. Second, variety nanostructures of ZnO can be fabricated through a simple, cheap and low temperature process, the low temperature sol-gel hydrothermal method. However ZnO nanostructures grown by hydrothermal method are reported to have considerable defects within bulk material and on surface and the efficiency of solar cells made with ZnO nanostructures as electrodes is very low. So in this project, we aimed to improve the crystalline quality and surface properties by annealing ZnO nanorods array. In my project, ZnO nanorods array was grow on FTO film which is coated on glass surface. Then distinct annealing treatments were applied to ZnO nanorods arrays and DSSC cells were assembled based on these substrates. Finally multi characteristics, like J-V testing, and analysis on efficiency vs morphology and efficiency vs annealing condition will be carried out.